2018
DOI: 10.3390/coatings8060226
|View full text |Cite
|
Sign up to set email alerts
|

ANN Laser Hardening Quality Modeling Using Geometrical and Punctual Characterizing Approaches

Abstract: Maximum hardness and hardened depth are the responses of interest in relation to the laser hardening process. These values define heat treatment quality and have a direct impact on mechanical performance. This paper aims to develop models capable of predicting the shape of the hardness profile depending on laser process parameters for controlling laser hardening quality (LHQ), or rather the response values. An experimental study was conducted to highlight hardened profile sensitivity to process input parameter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is found that scanning speed over 750 mm/s generate a relatively smooth hardened track, which is similar to the conventional laser hardened track using the first approach. In addition, models by extracting the punctual and geometrical attributes from the measured hardness profile are built to predict the shape of the hardness profile depending on the laser parameter for controlling laser hardening quality [14]. Furthermore, for the effect of surface topography on the laser energy coupling, Volpp et al [15] investigated the laser hardening of flat and curved surface and the corresponding hardening qualities.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that scanning speed over 750 mm/s generate a relatively smooth hardened track, which is similar to the conventional laser hardened track using the first approach. In addition, models by extracting the punctual and geometrical attributes from the measured hardness profile are built to predict the shape of the hardness profile depending on the laser parameter for controlling laser hardening quality [14]. Furthermore, for the effect of surface topography on the laser energy coupling, Volpp et al [15] investigated the laser hardening of flat and curved surface and the corresponding hardening qualities.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the rotation speed had an inverse effect on the surface hardness, but its effect on the hardened depth was negligible. Maamri et al [15] carried out experimental and numerical investigations to evaluate the sensitivity of the hardened pro les to the input parameters of the laser hardening process. They declared that the beam power and scanning speed had the highest impact on the quality of the process whereas the initial hardness of the material had less impact and the effect of the surface roughness was insigni cant.…”
Section: Introductionmentioning
confidence: 99%